Preparation, Structure and Biological Activities of Exopolysaccharides Produced by Enterobacter cloacae - Jin, M.L.; Zhao, K.; Huang, Q.S.; Shang, P. (Asian Journal of Chemistry, 2013)
Bacterial exopolysaccharides have been proved to have a wide range of health benefits effects. Enterobacter cloacae, a bacterial strain, can produce large amounts of exopolysaccharides. In the last few years, the exopolysaccharides produced by E. cloacae have attracted considerable research attention. Many studies on pharmacology have demonstrated that these macromolecules had various biological activities, such as immunomodulation, antioxidant, antitumor and antidiabetes. The aim of the present report is to summarize previous and current references and give a comprehensive summary of information regarding preparation, structural features as well as biological activities of these exopolysaccharides produced by E. cloacae.